Protections of transcription factor BACH2 and natural product myricetin against pathological cardiac hypertrophy and dysfunction - Jiang, Xueli; Cao, Mengying; Wu, Jian; Wang, Xiaolin; Zhang, Guoping; Yang, Chunjie; Gao, Pan; Zou, Yunzeng (Frontiers in Physiology, 2022)
Pathological hypertrophic myocardium under consistent adverse stimuli eventually can cause heart failure. This study aims to explore the role of BACH2, a member of the basic region leucine zipper transcription factor family, in cardiac hypertrophy and failure. Transverse aortic constriction (TAC) surgery was operated to induce cardiac hypertrophy and failure in mice. BACH2 was overexpressed in mice through tail vein injection of AAV9-Bach2. Mice with systemic or cardiac-specific knockdown of Bach2 were adopted. Neonatal rat ventricular myocytes (NRVMs) were isolated and infected with lentivirus to overexpress Bach2 or transfected with siRNA to knock down Bach2. Our data showed that overexpression of BACH2 ameliorated TAC-induced cardiac hypertrophy and failure in mice and decreased isoproterenol (ISO)-triggered myocyte hypertrophy in NRVMs. Systemic or cardiac-specific knockdown of Bach2 worsened the cardiac hypertrophy and failure phenotype in mice. Further assays showed that BACH2 bound to the promotor region of Akap6 at the -600 to -587 site and repressed its expression, which functioned as a crucial scaffold for cardiac hypertrophy and failure signaling pathways. Small molecular natural product library screening suggested that myricetin could up-regulate expression of Bach2 and simultaneously suppress the transcriptional levels of hypertrophic marker genes Bnp and Myh7. Further studies showed that myricetin exerted a BACH2-dependent protective effect against cardiac hypertrophy in vivo and in vitro. Taken together, our findings demonstrated that BACH2 plays a crucial role in the regulation of cardiac hypertrophy and failure and can be a potential therapeutic target in the future.